Hand exercises for patients with rheumatoid arthritis: an extended follow-up of the SARAH randomised controlled trial. Issue 4 (12th April 2017) - Williamson, Esther; McConkey, Christopher; Heine, Peter; Dosanjh, Sukhdeep; Williams, Mark; Lamb, Sarah E
Abstract : Objectives: The Stretching And strengthening for Rheumatoid Arthritis of the Hand (SARAH) randomised controlled trial evaluated the effectiveness of a hand exercise programme and demonstrated it was clinically effective and cost-effective at 12 months. The aim of this extended follow-up was to evaluate the effects of the SARAH programme beyond 12 months. Methods: Using postal questionnaires, we collected the Michigan Hand Questionnaire hand function (primary outcome), activities of daily living and work subscales, pain troublesomeness, self-efficacy and health-related quality of life. All participants were asked how often they performed hand exercises for their rheumatoid arthritis. Mean difference in hand function scores were analysed by a linear model, adjusted for baseline score. Results: Two-thirds (n=328/490, 67%) of the original cohort provided data for the extended follow-up. The mean follow-up time was 26 months (range 19–40 months). There was no difference in change in hand function scores between the two groups at extended follow-up (mean difference (95% CI) 1.52 (−1.71 to 4.76)). However, exercise group participants were still significantly improved compared with baseline (p=0.0014) unlike the best practice usual care group (p=0.1122). Self-reported performance of hand exercises had reduced substantially. Conclusions: Participants undertaking the SARAH exercise programme had improved hand function compared with baseline >2 years after randomisation. This was not the case for the control group. However, scores were no longer statistically different between the groups indicating the effect of the programme had diminished over time. This reduction in hand function compared with earlier follow-up points coincided with a reduction in self-reported performance of hand exercises. Further intervention to promote long-term adherence may be warranted. Trial registration number: ISRCTN89936343 ; Results.